Electrochemical Methods for Analysis of Hydroxide and Oxide Impurities in Li, Mg/Na, and Ca Based Molten Chloride Salts. (8th September 2020) - Gonzalez, Mario; Faulkner, Emma; Zhang, Chao; Choi, Suhee; Simpson, Michael Forrest
Abstract : Due to their highly hygroscopic nature, molten chloride salts are known to resist complete thermal dehydration, resulting in incomplete water removal prior to use in high temperature applications. At temperatures required to melt these salts, this can result in hydrolysis, leading to formation of oxides or hydroxides. Depending on application, these hydrolytic impurities can cause further adverse effects through the formation of insoluble oxides and oxychlorides. In this paper, previously published work is reviewed to discuss electrochemical methods used for identification and measurement of hydrolytic impurities in LiCl and CaCl2 as well as their effect on electrolytic processes. Cyclic voltammetry shows that thermal dehydration of LiCl and CaCl2 promotes LiOH and CaO formation, respectively. The presence of CaO in a CaCl2 -CeCl3 salt meant to emulate a typical actinide-chloride electrorefining salt causes insoluble Ce2 O3 and CeClO to form, reducing electrochemical signals as the active species is precipitated as an insoluble phase.